Effectiveness of Biosynthesized Silver Nano particles on Oral pathogens – A Systematic Review - V, Dr. ANNA NIREEKSHA; Fareed, Dr. Nusrath; B K, Dr. Rakshith; B, Dr. Suman (Indian Journal of Integrative Medicine, 2026)
Background: Silver nanoparticles (AgNPs) synthesized via biosynthesis have physicochemical properties and broad-spectrum biological activities and possess remarkable antimicrobial, anti-inflammatory, and wound-healing properties, making them useful in healthcare, pharmaceuticals, and dentistry. This systematic review aims to evaluate the effectiveness of biosynthesized silver AgNPs in promoting oral health by assessing their antimicrobial, antibiofilm, and biocompatibility properties in in vitro studies. Materials and Methods: A comprehensive literature search was conducted using PubMed and Science Direct databases up to May 2025. In vitro studies using biosynthesized AgNPs targeting oral pathogens were included. Only studies reporting measurable outcomes such as minimum inhibitory concentration (MIC), zone of inhibition (ZOI), biofilm reduction, or cytotoxicity were considered. The quality of the included studies was assessed using the QUIN (Quality Assessment Tool for In Vitro Studies). Results: Out of 1731 identified articles, 14 in vitro studies met the inclusion criteria. The biosynthesized AgNPs, showed significant antimicrobial effects against key oral pathogens. Reported MIC values ranged from 10.6 μg/ml to 50 μg/ml, and ZOI measurements varied between 9 mm and 29 mm. Few studies reported favorable cytotoxicity outcomes. However, quality assessment revealed that 13 out of 14 studies exhibited a high risk of bias due to methodological limitations. Conclusion: Biosynthesized AgNPs demonstrate promising antimicrobial potential and could serve as eco-friendly alternatives to conventional chemical-based oral antimicrobials.